KOMBINASI CANGKANG BIJI KARET DAN SEKAM PADI DALAM PEMBUATAN BRIKET SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BIOTEKNOLOGI SMA KELAS XII - Juana Prawita; Imam Mahadi; Yustina Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research was to determine the composition of the best combination of rubber seed shells and rice husk in manufacture of briquettes. The research was conducted in July to September 2019. The results of research were used as a worksheet design for student of conventional biotechnology grade XII senior high school. The research design was divided into two stages, namely the stage of making briquettes in combination of rubber seed shells and rice husk at the Laboratory of Teacher Training and Education Biology of Riau University, Laboratory of Mechanical engineering of Riau University, Laboratory of Minister Energy and Mineral Resources of Riau Province. The research using RAL consisting of 7 treatments and 3 replication. The student worksheet (LKPD) used ADDIE (Analyze, Design, Development, Implementation dan Evaluation) only reaches the stage design. Making briquettes in combination of rubber seed shells and rice husk consist of the preparation of raw materials, the carbonization stage, the stage reducing size, the stage of making briquettes dough and the stage of molding briquettes. The parameters in this research are water content, ash content, heating value, density and compressive firms. The result of the research was found that the P0 (9:1) treatment was the effective in making combination of briquettes rubber seed shells and rice husk. Then, the research were designed as a worksheet for conventional biotechnology student of senior high schoolKey Words: Student Worksheet, Rubber Seed Shells, Rice Husk, Briquettes.